How does competition enable social comparison? A comparison of behavior in competitive internet-based games - Lee, Yi-Hsuan; Chang, Wen-Ying; Li, ShangRu (Information technology and management, 2025)
This study investigated how different narcissistic personality types (grandiose and vulnerable) create differences in comparison behaviors. Taking social comparison theory as a starting point, this study extends the research on competitive games by exploring how different personalities operate in competitive contexts and analyzing the correlation between manifested behaviors and self-presentation tactics. This study adopted questionnaires and purposive sampling for analysis. Students from four higher education classes were the sample in the first survey, during which we hosted a Hole.io competition in order to have a preliminary understanding of participants’ social comparison and impression management behaviors in the context of a competitive game. For Survey 2, we employed the well-known game League of Legends to investigate its players’ social comparison and self-presentation tactics. Differences were found in the upward and downward comparison tendencies of different personalities in the first and second surveys. In the area of impression management, both surveys found that upward and downward comparison behaviors related to different self-presentation tactics.